IDENTIFYING CAUSES OF DELAY IN OIL AND GAS CONSTRUCTION PROJECTS USING FUZZY DELPHI METHOD (Globalization and Business, 2018)
One of the challenges project managers are dealt with is management of delay in construction projects. Organizations particularly pay special attention to the efficient manage-ment of projects and make a lot of efforts to achieve this goal by reducing delay in projects. Analyzing the factors causingdelay is essential with the aim of omitting them and timely implementation of these projects. On account of the impor-tance of oil and gas projects, in this research the factors caus-ing delay in oil and gas construction projects are taken in to the consideration. These factors are identified by using fuzzy Delphi method.